Louise Artus-Perrelet e o ensino do desenho : uma proposta de educação estética para formação de professores no início do século XX - Marilene Oliveira Almeida (2020)
This doctoral research aimed to know and analyze a drawing teaching proposal arranged by Louise Artus-Perrelet (1867-1946) in the book Le dessin au service de l’éducation (1917). Artus-Perrelet worked at Belo Horizonte Teachers College between 1929 and 1931. She held lectures and an educational drawing and games course for primary teachers in Rio de Janeiro. The research sought to understand her drawing teaching method in terms of aesthetic education for primary teachers training in the early twentieth century under the modernist art tendencies and the New School principles. Thereunto, inedited sources were analyzed, such as Brazilian newspapers, most of the reports published by Cecília Meireles on Pagina de Educação of the newspaper Diario de Noticias; Swiss newspapers; awards reports; teaching programs; manuscripts and mails exchanged between characters related to art and education of that time. Barthélemy Menn (1815-1893) student at École des Beaux-Arts in Geneva, Artus-Perrelet was disciplined in a context of association between visual arts and applied arts. Menn would have encouraged her education path inducing the belief of knowledge as a basis for creation. The Artus-Perrelet method dialogued with the teaching process of artists as Paul Klee (1879-1940) and Wassily Kandinsky (1866-1944), and Bauhaus School teachers (1919- 1933), combining art, handcrafting and architecture. Data reaffirmed that Artus-Perrelet’s pedagogy joined the principles of functional education and experimental pedagogy originated inside the Jean-Jacques Rousseau Institute (1912), where she was one of the first professors along with Édouard Claparède (1873-1940) and Pierre Bovet (1878-1944). For Artus-Perrelet the drawing teaching should have a relationship with the daily routine and it should be integrated by all the artistic languages. The drawing basic concepts should be understood through body activities or symbolic games. The synthetic capitation of form would be stimulated over the perception and intuition in the direct relation with object and nature. The graphic design expression would be the consequence of this process.